Intervención del terapista respiratorio en paciente masculino de 82 años de edad con diagnóstico de enfermedad pulmonar obstructiva crónica. - Zeas Jorgge, Marileydi (2022)
Through this work, everything about Chronic Obstructive Pulmonary Disease (COPD), its etiology, pathophysiology, risk factors, clinical picture, diagnosis and treatment will be revealed. COPD is a disease that worries health organizations due to its high mortality rate in the world. It is estimated that by 2030 it will be the third leading cause of death worldwide. A correct assessment of the clinical picture presented by the patient, in addition to the complementary tests carried out such as blood gases and chest X-ray, help to make a correct diagnosis in patients with suspected chronic obstructive pulmonary disease. At the end of this study, a clinical case was established, it was concluded that smoking was the main triggering factor for the development of this disease, so that the main basis of COPD treatment is smoking cessation, which must be completed with pharmacological treatment. Since this disease has no cure, proper and timely control will prevent complications for the patient's health.